Mapping teachers’ awareness of artificial intelligence in the changing education paradigm: insights from a mixed methods inquiry - Bulut, Ramazan (Frontiers in Psychology, 2026)
The proliferation of artificial intelligence (AI) tools, which reflect the rapid advancements in technology, has led to their widespread use in various fields, including health, finance and education. The effective and efficient use of AI tools in education is closely related to teachers’ awareness in this regard. The objective of this study is to comprehensively ex-amine the AI awareness status of teachers by employing a mixed-method approach. The present study is designed based on a triangulation design and is conducted with a sample of 260 teachers. The findings of the study demonstrate that teachers have a moderate level of AI awareness, and that this awareness improves through AI tool use, receiving training, following publications, and daily internet use. The qualitative findings of the study corroborate the quantitative findings in that they also demonstrate that teachers have limited awareness of conceptual perception, educational use, and positive–negative effects concerning AI tools. The findings further indicate that the majority of educators acknowledge the benefits of AI while also expressing concerns about its limitations, resulting in an ambivalent perception. The prevailing opinion among educators is that AI is not yet capable of replacing teachers due to its inability to replicate affective skills such as empathy and building rapport. However, it is also reported that the effectiveness of this phenomenon is contingent upon conscious utilization.